2000
DOI: 10.3406/reae.2000.1632
|View full text |Cite
|
Sign up to set email alerts
|

Family and non-family succession in the Upper-Austrian farm sector

Abstract: Comprendre la transmission des exploitations agricoles est essentiel pour analyser les changements structurels du secteur agricole. Grâce à des données de recensements apariées de 1980, 1985 et 1990, les décisions de succession des ménages ruraux de Haute-Autriche sont examinées empiriquement en utilisant un logit multinomial. Contrairement aux enquêtes auprès des exploitations qui examinent les projets de succession, le recensement des exploitations permet d'identifier des successions ayant réellement eu lieu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…This implies that an increase in farming experience, years of residency, and cash crop farming activities will also increase the intention of aged farmers to have a succession plan. This established that increase in the farming experience as reported by Stiglbauer and Weiss, (2000); Vogel, (2007); Glauben et al (2009) has an increasing effect on a succession plan.…”
Section: Test Of Hypothesesmentioning
confidence: 60%
“…This implies that an increase in farming experience, years of residency, and cash crop farming activities will also increase the intention of aged farmers to have a succession plan. This established that increase in the farming experience as reported by Stiglbauer and Weiss, (2000); Vogel, (2007); Glauben et al (2009) has an increasing effect on a succession plan.…”
Section: Test Of Hypothesesmentioning
confidence: 60%
“…Therefore we used a proxy to capture the event of succession: we identified an event of succession based on managers' age differences between two consecutive years. The change in manager's age is widely used to identify a succession event both in non-agricultural firms (Bach, 2010;Bach and Serrano-Velarde, 2015;Bates et al, 2000;Colombo et al, 2014) and in the farm sector (Kimhi and Bollman, 1999;Remble et al, 2010;Stiglbauer and Weiss, 2000). Furthermore, documents based on official statistics (Allen and Harris, 2005), as well as expert opinions and direct interviews with farmers in Italy collected by us, support the reliability of age difference to approximate a succession event.…”
Section: Data and Proxy For Farm Successionmentioning
confidence: 72%
“…For example, Zhengfei and Oude Lansink (2006) suggested that there is an adjustment period of newly settled farmers, where they get into debt and invest to expand, maybe impacting negatively farm performance. The presence of a successor on the farm before succession takes place may influence future farm strategies in a positive way and limit this decrease in performance, since younger farmers are generally more oriented toward diversifying farm activities and adopting more sustainable agricultural practices (Sottomayor et al, 2011;Stiglbauer and Weiss, 2000;Suess-Reyes and Fuetsch, 2016;Zagata and Sutherland, 2015). In addition, some actions taken by the retiring farmer before transfer, and aiming at developing the farm and improving performance, can also make the farm more attractive to successors (Cavicchioli et al, 2015;Lobley and Baker, 2012) and ensure its viability (Wheeler et al, 2012).…”
Section: The Specific Case Of Farm Businessesmentioning
confidence: 99%
“…Entering the family farming system McGreevy et al (2019, p. 226) present two fundamental routes into family farming by generational change: via heritage-family farming offspring succeeds immediately or delayed by interim education or occupation outside of agriculture, and via non-heritage-newcomers with specific agricultural education and practice or complete autodidacts without prior farming expertise take over (cf. Korzenszky, 2018;Stiglbauer & Weiss, 2000). Zagata et al (2017, p. 18ff) label successors who have not grown up on a farm as 'new entrants' and thus differentiate them clearly from 'young farmers' who were raised on a family farm, are usually working there already and take over directly.…”
Section: Determinants Of Generational Renewalmentioning
confidence: 99%
“…(2019, p. 226) present two fundamental routes into family farming by generational change: via heritage—family farming offspring succeeds immediately or delayed by interim education or occupation outside of agriculture, and via non‐heritage—newcomers with specific agricultural education and practice or complete autodidacts without prior farming expertise take over (cf. Korzenszky, 2018; Stiglbauer & Weiss, 2000). Zagata et al.…”
Section: Literature Reviewmentioning
confidence: 99%